Analytical data for manganese nodules retrieved from selected areas in the equatorial and SW Pacific - Glasby, Geoffrey P; Thijssen, Theo (PANGAEA, 2023)
The composition of the acid-insoluble residue and hydrolysate fraction has been determined for manganese nodules retrieved along an equatorial Pacific transect surveyed during campaigns COPANO of R/V Le Suroit and SO-06 of R/V Sonne as part of the I.C.I.M.E. (International Cooperative Investigations of Manganese Nodule Environments) Project. In order to determine the percentage of acid-insoluble residue and the composition of the hydrolysate fraction in the manganes nodules, a bulk chemical analysis of the was first carried out. The samples were dried for 48 hours at 105°C. 0.5 g of each sample was then treated with 10 mls of HF/HNO3/HCl in a 5/2/3 mixture in a water bath for one hour at 80°C. 50 mls of saturated boric acid were added in the solution heated again for one hour in the water bath. The solution was then made up to 100 ml with distilled water and the resultant solution analyzed by atomic absorption spectrophotometry.
Keywords: Geochemistry; manganese micronodule; manganese nodule; ocean; Sediment